Syntheses of functionalized benzocoumarins by photoredox catalysis. Issue 6 (12th January 2023) - Lai, Qihong; Chen, Shanyi; Zou, Linnan; Lin, Chengzhi; Huang, Shuling; Fu, Lailing; Cai, Lina; Cai, Shunyou
Abstract : We report a new method for the synthesis of functionalized benzocoumarins through the strategy of activation of multiple C–H bonds on 2-aryl toluenes under visible-light-enabled photoredox conditions. Abstract : Direct functionalization of inert C(sp 3 )–H bonds is an attractive synthetic technology for the preparation of pharmaceutically significant compounds in modern synthetic organic chemistry. In this work, we report a new method for the synthesis of functionalized benzocoumarins through the strategy of activation of multiple C–H bonds on 2-aryl toluenes under visible-light-enabled photoredox conditions. This method has the advantages of high functional group compatibility, mild reaction conditions, and effectively avoiding the use of strong oxidants and precious metal catalysts. Detailed mechanistic investigations, including spectroscopic and electrochemical studies, support the reaction's mechanistic course.